Transient Receptor Potential Melastatin 7 (TRPM7) Contributes to H2O2-Induced Cardiac Fibrosis via Mediating Ca2+ Influx and Extracellular Signal-Regulated Kinase 1/2 (ERK1/2) Activation in Cardiac Fibroblasts - Jin-Lei Guo; Yang Yu; Yan-Yan Jia; Yun-Zi Ma; Bo-Yu Zhang; Pei-Qing Liu; Shao-Rui Chen; Jian-Min Jiang (Elsevier, 2014)
Abstract.: Transient receptor potential melastatin 7 (TRPM7), a Ca2+-nonselective cation channel, plays a key role in the pathophysiological response of multiple cell types. However, the role of TRPM7 channels in hydrogen peroxide (H2O2)-induced cardiac fibrosis remains unclear. This study aimed to explore whether TRPM7 channels are involved in H2O2-induced cardiac fibrosis and the underlying mechanisms. Our results showed that 2-aminoethoxydiphenylborate (2-APB), which is commonly used to block TRPM7 channels, inhibited H2O2-induced cardiac fibrosis via attenuating the overexpression of important fibrogenic biomarkers and growth factors in cardiac fibroblasts, including collagen type I (Col I), fibronectin (FN), smooth muscle α-actin (α-SMA), connective tissue growth factor (CTGF), and transforming growth factor-β1 (TGF-β1). In addition, 2-APB also decreased H2O2-mediated elevation of the concentration of intracellular Ca2+ ([Ca2+]i). Meanwhile, silencing TRPM7 channels by shRNA interference also impaired the increased [Ca2+]i and upregulation of Col I, FN, α-SMA, CTGF, and TGF-β1 induced by H2O2. Furthermore, we found that H2O2-mediated activation of extracellular signal-regulated kinase 1/2 (ERK1/2) decreased in TRPM7-shRNA cells and Ca2+-free culture media. These results demonstrated that TRPM7 channels contributed to H2O2-induced cardiac fibrosis and suggested that this contribution may be through mediating Ca2+ influx and phosphorylation of ERK1/2. Keywords:: cardiac fibrosis, H2O2, Ca2+ signal, transient receptor potential melastatin 7 (TRPM7), extracellular signal-regulated kinase 1/2 (ERK1/2)